A New Aliphatic Glycoside Constituent from the Hairy Root Cultures of Catharanthus roseus - CHUNG, ILL-MIN; KIM, JONG-JIN; CHUN, SE-CHUL; AHMAD, ATEEQUE (Asian Journal of Chemistry, 2010)
A new long chain aliphatic glycoside (n-heptacosan-13α-ol- 13β-D-glucopyrasnoside) along with known compounds, n-hentetracont-36-en-5β-ol and β-sitosterol were isolated from the methanolic extract of the cultured hairy roots of Catharanthus roseus. The structures of these compounds were elucidated by a combination of spectral methods (IR, EIMS, FABMS, 1H and l3C NMR). To the best of our knowledge, n-hentetracont-36-en-5β-ol was identified for the first time from the hairy roots of C. roseus.